Effect of Prison Based Alcohol Treatment: Treatment and Recidivism Data from Montana, Ohio, and Texas, 2006-2012 - Miller, Mitch ([Verlag nicht ermittelbar], 2017)
This study evaluated program design, quality of treatment delivery, and program effectiveness of three separate state sponsored alcohol specific treatment programs in prisons located in Montana, Ohio, and Texas from 2006 to 2012.